RELATIONSHIP BETWEEN FACTORS AFFECTING THE IMPLEMENTATION OF OCCUPATIONAL SAFETY AND HEALTH AT HOSPITAL X - ZUNIAWATI, DEWI; Pringgotomo, Gathut (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
Background: Occupational Safety and Health (OHS) services are a crucial aspect in creating a safe and healthy work environment, especially in hospitals that have a high potential for physical, chemical, biological, ergonomic, and psychosocial hazards. The Hospital OHS Service is one of the efforts to improve the quality of Hospital services, particularly in terms of health and safety for hospital staff, patients, visitors/patient escorts, and the surrounding community. According to the guidelines of the Minister of Health Regulation No. 66 of 2016 concerning Hospital Occupational Safety and Health, it is stated that OHS Service efforts must be implemented in all workplaces, especially workplaces that have a risk of health hazards and are easily infected by disease. Method: Observational with a cross-sectional study approach Result: The results of the study showed that there was a significant relationship between knowledge (p=0.000), training (p=0.000), workload (p=0.012), and length of service (p=0.003) with the implementation of occupational health and safety at Hospital X. Conclusion: It is hoped that employees will always follow the hospital's occupational health and safety guidelines so that in carrying out their duties work accidents can be avoided..